Exploring the role of NOD2 variants in pediatric undifferentiated recurrent fever: a clinical and functional perspective - Taşkın, Raziye Burcu; Kamiloğlu, Arzum Hande; Bara, Buşra; Akyol, Gizem; Aydın, İlyas; Aytac, Gulcin; Karaca, Neslihan Edeer; Aksu, Güzide; Berdeli, Afig; Bozok, Vildan; Kütükçüler, Necil (Frontiers in Immunology, 2025)
IntroductionSyndrome of Undifferentiated Recurrent Fever (SURF) is an autoinflammatory disorder with onset in childhood, marked by recurrent episodes of fever without an established molecular diagnosis. Although NOD2 gene variants that are generally considered non-pathogenic are often identified in these patients, their contribution to disease development is still not well understood.MethodsThis study aimed to assess the clinical characteristics, long-term progression, and functional implications of NOD2 variants in a group of twelve children diagnosed with SURF, along with two Blau syndrome cases and two healthy controls. Clinical information was gathered at presentation and during follow-up. Peripheral blood mononuclear cells were examined for cytokine secretion and NF-kB pathway activation, both at baseline and following muramyl dipeptide stimulation, using multiplex cytokine analysis, Western blot, and ELISA.ResultsThe median follow-up period was 3.75 years, with most children developing symptoms before 10 years of age. Abdominal pain and limb pain were the most frequent complaints. All patients were treated with colchicine, and selected cases required corticosteroids or disease-modifying antirheumatic drugs. Elevated levels of proinflammatory cytokines, including IL-2, TNF-a, IL- 6, and IL-8, were observed in SURF patients. Our functional studies suggested that variants like R702W, G908R, P268S/V955I, and R702W/P268S might have triggered stronger inflammatory responses, whereas L682F, L1007fs, and R587C might have been linked to diminished cytokine production and lower NF-kB activity. Certain variants, such as A1000T and P268S, appeared to show baseline NF-kB activation with moderate inflammatory activity.DiscussionOur findings emphasize the clinical and functional diversity of NOD2 variants in SURF and may point to a possible genotype–phenotype relationship that could aid in understanding disease pathways and refining diagnostic approaches.